PENGEMBANGAN APLIKASI NOTIFIKASI MASA STUDI MAHASISWA UIN AR RANIRY BERBASIS ANDROID - Akram, Muhammad; Dewi, Sarini Vita (Jurnal Teknologi Informasi Mura, 2026)
Universitas Islam Negeri (UIN) Ar-Raniry Banda Aceh is one of the leading State Islamic Religious Universities in Indonesia that sets a maximum seven-year study period for undergraduate programs. However, the current delivery of information regarding study period limits and credit achievement is still conventional and not proactive, causing many students to be unaware of their remaining study period and the number of credits that must still be completed, which risks leading to academic dropout. To address this problem, an Android-based student study period notification application was developed with an integrated full-stack architecture. This research uses the Research and Development (R&D) method with the Waterfall model which includes requirements analysis, system design, implementation, testing, and maintenance stages. The application was developed using Flutter as front-end, FastAPI as back-end, and PostgreSQL as database. System testing was conducted using Black-Box Testing on 28 test scenarios. The research results show that all application features function according to specifications, including real-time notification delivery to students, so this system will be able to increase student awareness of remaining study period and credit achievement, and has the potential to reduce dropout risk and support on-time graduation.